Metode Ordinary Kriging Menggunakan Semivariogram Isotropik dalam Menghitung Curah Hujan Kota Padang - Anshari Luthfi Maulana Achiar; Helma Helma (UNIVERSITAS NEGERI PADANG, 2019)
Abstract Kriging is a geostatistical method to predict a spacial object with unknown value based on another spacial object with known value. Kriging becomes semivariogram model to achieve optimum prediction by using the influence of spacial correlation. Counting rate of rainfall in forecast was one of the special problem in geostatistic. During its measurement, Meteorological Climatological Geophysical Agency (BMKG) was having financial and post obstacles that some districts did not have the rainfall observation center. That condition blocks kriging method in counting the rate on that area. One of the Kriging method used was ordinary kriging conducted for stationary data without outlier to produce a BLUE (Best Linier Unbiased Estimator) prediction. The aim of this research is to predict Padang city rate of rainfall on June 2018 within each district and subsdistrict. Keywords Kriging, Semivariogram, Rainfall.